2013
DOI: 10.1002/etc.2220
|View full text |Cite
|
Sign up to set email alerts
|

The spring runoff in nebraska's (USA) Elkhorn River watershed and its impact on two sentinel organisms

Abstract: The objectives of the present study were to determine 1) if temporal variability influenced the toxicity of Elkhorn River water and 2) if the toxic effect was consistent between two sentinel organisms, the fathead minnow (Pimephales promelas) and the northern leopard frog (Rana pipiens). During spring 2012, atrazine indicator strips were used to document the occurrence of agrichemical pulses in the Elkhorn River. Polar organic chemical integrative samplers (POCIS) were deployed for 14 d during both a pulse and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 27 publications
(53 citation statements)
references
References 43 publications
3
48
2
Order By: Relevance
“…Briefly, beginning April 15, 2015 atrazine test strips were used to test whether concentrations of atrazine in surface water in the Elkhorn River were above or below 3 μg·L . These test strips have been demonstrated to accurately detect the presence of atrazine and other triazine herbicides at 3 μg·L −1 in surface water (US EPA 2004), with further confirmation of there accuracy by previously collected field data (Knight et al 2013;Ali and Kolok 2015). Tests were conducted every three to four days where the detection of three consecutive positive atrazine strips determined the start of the spring agrichemical pulse on May 8, 2015 (Fig.…”
Section: Exposure At the Elkhorn River Research Stationmentioning
confidence: 58%
See 4 more Smart Citations
“…Briefly, beginning April 15, 2015 atrazine test strips were used to test whether concentrations of atrazine in surface water in the Elkhorn River were above or below 3 μg·L . These test strips have been demonstrated to accurately detect the presence of atrazine and other triazine herbicides at 3 μg·L −1 in surface water (US EPA 2004), with further confirmation of there accuracy by previously collected field data (Knight et al 2013;Ali and Kolok 2015). Tests were conducted every three to four days where the detection of three consecutive positive atrazine strips determined the start of the spring agrichemical pulse on May 8, 2015 (Fig.…”
Section: Exposure At the Elkhorn River Research Stationmentioning
confidence: 58%
“…Exposure of all fathead minnow larvae was conducted at the Elkhorn River Research Station (ERRS) where previous field studies have identified biological impacts and changes in endocrine responsive gene expression following in situ exposure to agricultural runoff (Knight et al 2013;Ali and Kolok 2015;Zhang et al 2015;Ali et al 2016). The ERRS is an open-air facility located approximately 10 km upstream from the confluence of the Elkhorn and Platte Rivers, Nebraska, USA.…”
Section: Exposure At the Elkhorn River Research Stationmentioning
confidence: 99%
See 3 more Smart Citations